Anti theft compact sedan / Mohamad Danish Mohamad Faizal - Mohamad Faizal, Mohamad Danish (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Creating revolutionary advanced safety features incident response for semi-autonomous compact sedan vehicle which automate incident response processes , such as isolation compromised system / threats and barrier shield defense to prevent further damage . Thermal camera and ignition kill switches off will be add on . Imagine arriving at your parking spot and discovering it is empty. horrifying, isn't that right? It may seem like one of those "it won't happen to me" situations when your car is stolen. Car theft, however, occurs more frequently than you might think. Vehicle theft is categorized as a property crime, also known as a highly organized crime and is one of the many global issues affecting the world, including Malaysia.. In Malaysia, there are approximately 18 million registered vehicles and vehicle owners are required to purchase motor insurance. As we know, the world is currently moving towards advanced technology, from industry-based to society's daily needs. With the technological capabilities we currently possess, it will be able to assist in resolving and decreasing the number of car theft cases that are currently occurring. Using AI technology to stop auto theft is a practical strategy that is becoming more and more popular. AI-powered solutions have many benefits for improving car security and lowering the chance of theft.